Pengaruh Motivasi, Disiplin dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada BCA Kcp Grand Wisata – Bekasi - Theresia Winarti; Rakhmat; Asrul (Mulia Pratama, 2023)
This study aims to determine the effect of motivation, discipline, and the environment on employee performance either partially or simultaneously. The population sample in this study were all employees who worked at the BCA Grand Wisata City Branch, totaling 45 people. Based on the test results, it can be seen that the tcount for the motivation variable is 6.079 which is greater than the ttable value, namely 2.020 (6.079 ? 2.020) while the sig value for the motivation variable is less than 0.05 (0.000 ? 0.05). While the tcount for the discipline variable is 2.848 which is greater than the ttable value of 2.020 (2.848 ? 2.020) and the sig value is less than 0.05 (0.041 <0.05). The effect of the work environment on employee performance, based on the test results it can be seen that the tcount value for the work environment variable is 2.359 which is greater than the ttable value of 2.020 (2.359 > 2.020) with a sig value less than 0.05 (0.022 <0.05). The influence of motivation, discipline and work environment on employee performance based on the results of SPSS 23 calculations shows a significance value of 0.000 <0.05 and an Fcount value of 61.827 > 2.83. The conclusion from this study is that it means that motivation influences employee performance. The discipline variable also influences employee performance, so it can be interpreted that the higher the level of employee discipline, the better/increased employee performance, vice versa, the lower the level of employee discipline, the lower employee performance. Work environment variables affect employee performance, so it can be interpreted that the better the employee's work environment, the better the employee's performance. Then the variables of motivation, discipline and work environment have a simultaneous influence on employee performance, the higher the motivation, discipline and work environment the more conducive, the higher the employee performance. The coefficient of determination (R2) in this study is 0.806 or 80.6% which means that employee performance variables can be explained by motivation, discipline and work environment variables of 80.6%, while the remaining 10.4% is influenced by other variables outside this research mode.